Pengaruh Likuiditas, Profitabilitas dan Corporate Social Responsibility Terhadap Agresivitas Pajak (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar Di BEI Tahun 2018-2020) - Saraswati Novi Yuliantoputri; Dahli Suhaeli (Borobudur Management Review, 2022)
This study aims to examine and analyze how much liquidity, profitability and corporate social responsibility influence fiscal aggression. The sample in this study is a food and beverage subsector listed on the Indonesian Stock Exchange in 2018-2020. The number of in this study based on the purposive sampling method is 25 companies multiplied by the observation year to obtain 75 data. The data analysis method in this study used multiple linear regression. The results of this study indicate that liquidity, profitability and corporate social responsibility simultaneously have a significant effect on fiscal aggression. Meanwhile, liquidity and partial profitability have a negative and significant effect on fiscal aggression, and corporate social responsibility has a positive and insignificant effect on fiscal aggression.